Quality of Life in Patients with CKD With Catastrophic Health Care Expenditures: A National Study From Thailand - Pornpen Sangthawan; Sarayut L. Geater; Pinkaew Klyprayong; Pimwara Tanvejsilp; Sirirat Anutrakulchai; Pongsathorn Gojaseni; Charan Kuhiran; Pichet Lorvinitnun; Kajohnsak Noppakun; Watanyu Parapiboon; Adisorn Pathumarak; Supinda Sirilak; et al. (Kidney Medicine, 2025)
Rationale & Objective: Despite universal health coverage, patients with chronic kidney disease (CKD) in middle-income nations still face financial hardship. Catastrophic health care expenditures (CHEs) serve as a valuable index of patient-derived financial hardship, but few studies have explored the connection of CHE with clinical correlates, especially in patients with CKD. This study aimed to assess the association between CHE and health-related quality of life (HRQoL) in a spectrum of patients with CKD in Thailand. Study Design: A multicenter, nationwide cross-sectional study. Setting & Population: Patients with CKD (stages 3-5 and dialysis) from 11 centers across Thailand. Exposures: Catastrophic health expenditures. Outcomes: Health-related quality of life. Analytical Approach: Data on clinical, socioeconomic status, and out-of-pocket expenses were acquired via interviews. The CHE was defined as health care expenditures of at least 40% of the household’s capacity to pay. The HRQoL was assessed using the EuroQol-5 Dimensions (EQ5DL) questionnaire. Fractional and multivariable logistic regression models were used to determine the CHE’s effect on EQ5DL composite utility scores and each HRQoL dimension. Results: Of 1,224 patients with CKD, 20% experienced CHE. EuroQol-5 Dimensions utility scores were notably lower in those with CHE (CHE, 0.76 vs No CHE, 0.82, P < 0.001) after adjustments for confounding factors. Differences between CHE and non-CHE appeared in mobility, self-care, and usual activity, with multivariable analysis showing more severe mobility and activity issues in CHE. (adjusted OR [95% CI] in CHE vs non-CHE: mobility: 1.89 [1.23-2.91], P = 0.004; usual activity: 1.82 [1.10-3.02], P = 0.020]. Limitations: Cross-sectional design prevents causal inferences. Conclusions: Despite health coverage, patients with CKD with financial strain experience reduced quality of life, with pronounced effects on mobility and daily activity. Integrating the assessment of patient-derived financial burden is an essential step into CKD care plans in middle-income countries. Plain Language Summary: Patients with chronic kidney disease (CKD) often face substantial out-of-pocket payments for their care. This study aimed to understand how catastrophic health care expenditures (CHE) affect CKD patients' quality of life. CHE occurs when medical costs overwhelm a household's finances. We conducted a nationwide study in Thailand to examine how CHE affects patients with CKD’s well-being, focusing on mobility, daily activities, and emotional health. By analyzing data from patients across different stages of CKD, we found that patients experiencing CHE reported significantly lower quality of life than those without CHE. Our findings identify the need to address financial hardship in CKD care, emphasizing integrated support strategies such as financial planning and assistance to reduce the burden of CHE on daily life.